The illusion of a green transition in Slovenia by 2050 - Senegačnik, Andrej (Strojniški vestnik, 2024)
This study analyzes the possibilities of phasing out fossil and nuclear energy sources for Slovenia by 2050. Alternative carbon-free sources include renewable energy sources (RES) i.e. electricity, synthetic fuels and hydrogen from water electrolysis. The model is based on the use of currently mature low-carbon technologies and is adapted to Slovenia’s natural conditions. Photovoltaic panels (PV) and hydropower plants are used for the majority of renewable electricity generation. To bridge the winter period with minimal PV production, storage with a pumped storage power plant is planned. One of the assumptions of the national climate strategy has been incorporated into the model, which envisages zero growth in final energy consumption by 2050. The result of the paper is an assessment of what some of the basic characteristics of the Slovenian energy system would look like after the phase-out of fossil and nuclear energy sources. The estimated storage capacity required is 5.1 MWh/capita. Abandoning fossil fuels with the currently mature RES technologies is not realistically feasible for technical and economic reasons.
Keywords: črpalno akumulacijske hidroelektrarne; energijska samozadostnost; fotonapetostni sistemi; green transition; obnovljivi viri energije; opustitev fosilnih goriv; opustitev jedrske energije; phasing out fossil energy sources; phasing out nuclear energy sources; photovoltaic modules; pumped hydro storage; renewable energy sources; zeleni prehod